Designing Photochromic Materials with Large Luminescence Modulation and Strong Photochromic Efficiency for Dual‐Mode Rewritable Optical Storage. Issue 20 (16th July 2021) - Yang, Zetian; Du, Jiaren; Martin, Lisa I. D. J.; Feng, Ang; Cosaert, Ewoud; Zhao, Bo; Liu, Wanlu; Van Deun, Rik; Vrielinck, Henk; Poelman, Dirk
Abstract: Inorganic materials combining photochromism and luminescence modulation characteristics have great potential in dual‐mode rewritable optical storage due to their unique optical features and excellent thermal stability. However, the failure of achieving a large luminescence modulation and a strong photochromic efficiency in photostimulated inorganic photochromic materials limits their applications. Herein, a new strategy for realizing an overlap between the photochromic absorption peak and the photoluminescent emission/excitation peak is proposed for designing high‐performance photochromic materials. The obtained BaMgSiO4 : M (M = Ce 3+, Mn 2+, or Nd 3+ ) ceramics exhibit a reversible white‐pink color change upon alternate 310 nm and 590 nm illumination (or thermal stimulus) accompanied by a high photochromic efficiency (>50%). Benefiting from a perfectly matched photochromic absorption peak and Mn 2+ emission peak, a record luminescence modulation of 96.3% with excellent fatigue resistance is obtained in BaMgSiO4 : Mn 2+ ceramics. These properties are superior to all photochromic materials reported to date, demonstrating great potential in optical information storage applications. The trap‐related photochromic and regulated luminescence behavior is investigated together with a prototype of a dual‐mode information display. This work is expected to promote the practical application of photochromic materials in various optical devices and provides an effective strategy to develop other photochromic materials. Abstract : A new strategy of constructing a perfect overlap between the photochromic absorption peak and the photoluminescent emission/excitation peak is reported to design high‐performance photochromic materials. Both a record luminescence modulation of 96.3% and a high photochromic efficiency of 53.5% are achieved in BaMgSiO4 : Mn 2+ ceramics, showing great promise in dual‐mode optical information display.